Inside Cover: Monitoring Binding of HIV‐1 Capsid Assembly Inhibitors Using 19F Ligand‐and 15N Protein‐Based NMR and X‐ray Crystallography: Early Hit Validation of a Benzodiazepine Series (ChemMedChem 3/2013). Issue 3 (22nd February 2013) - Goudreau, Nathalie; Coulombe, René; Faucher, Anne‐Marie; Grand‐Maître, Chantal; Lacoste, Jean‐Eric; Lemke, Christopher T.; Malenfant, Eric; Bousquet, Yves; Fader, Lee; Simoneau, Bruno; Mercier, Jean‐François; Titolo, Steve; et al.
<x xml:space="preserve">Abstract</x> Mature HIV‐1 capsid (CA) core is characterized by a fullerene cone‐shaped structure made of hexamers and pentamers. Inhibition of its assembly is a novel mechanism through which to target HIV‐1. The inside cover picture shows the characterization of potent CA assembly inhibitors (orange) as N‐terminal domain (NTD) binders using 19F NMR and X‐ray co‐crystallography. For more details, see the Full Paper by Nathalie Goudreau, René Coulombe et al. on p. 405 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>